2011
DOI: 10.1111/j.1365-294x.2011.05214.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the root‐associated fungal communities along a primary succession gradient analysed by 454 pyrosequencing

Abstract: We investigated changes in the root-associated fungal communities associated with the ectomycorrhizal herb Bistorta vivipara along a primary succession gradient using 454 amplicon sequencing. Our main objective was to assess the degree of variation in fungal richness and community composition as vegetation cover increases along the chronosequence. Sixty root systems of B. vivipara were sampled in vegetation zones delimited by dated moraines in front of a retreating glacier in Norway. We extracted DNA from rins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
171
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(183 citation statements)
references
References 78 publications
(100 reference statements)
9
171
3
Order By: Relevance
“…In contrast to other studies (see, for example, Blaalid et al, 2012;Brown and Jumpponen, 2014), we did not observe a clear directional shift in the fungal communities across successional stages. This was mostly because of the extreme abundance of the OTU affiliated with M. anisopliae at stage 35, which may indicate a high abundance of either the hyphal or spore forms.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In contrast to other studies (see, for example, Blaalid et al, 2012;Brown and Jumpponen, 2014), we did not observe a clear directional shift in the fungal communities across successional stages. This was mostly because of the extreme abundance of the OTU affiliated with M. anisopliae at stage 35, which may indicate a high abundance of either the hyphal or spore forms.…”
Section: Discussioncontrasting
confidence: 56%
“…Understanding fungal community turnover at local and regional scales is critical to explain ecological succession Microbial ecologists have only recently started to investigate the patterns of microbial community dynamics in natural systems (see, for example, Nemergut et al, 2007;Blaalid et al, 2012;Brown and Jumpponen, 2014;Dini-Andreote et al, 2014). As changes in microbial community composition are often associated with variations in the functional capabilities of the communities (Fierer et al, 2007;Salles et al, 2009), unravelling the temporal turnover patterns is crucial for understanding ecosystem processes.…”
Section: Discussionmentioning
confidence: 99%
“…In plants of the Tyrolean Rotmoos glacier forefront, , and in the Bavarian Alps, Garnica et al (2012) found S. incrustans and several unnamed species of Sebacinales as ECM fungi in B. vivipara. Changes in the root-associated fungal communities along a primary succession gradient, analyzed by 454 pyrosequencing, has shown Basidiomycota, including Sebacina, as the dominant fungi by the numbers of OTUs and sequences (Blaalid et al 2012). Tremelloscypha gelatinosa has been reported for the first time from Yucatan, Mexico by Guzman (2004).…”
Section: Sebacinalean Ectomycorrhizae (Ecm)mentioning
confidence: 99%
“…The PLFA method has some misuse or misinterpretation to the specificity of signature PLFA and to what extent such PLFA are found in living microorganisms (Frostegård et al 2011). 18S rRNA genes are known to be too conserved to provide good separation of fungal taxa, and fungal-specific taxa should use the primers of ITS region of rRNA genes (e.g., Blaalid et al 2012;Xu et al 2012;Clemmensen et al 2013). Hence, more scientific methods will be applied in further research to make more accurate identification of microbial taxa.…”
Section: Effects Of Moisture and Straw Availability On Microbial Commmentioning
confidence: 99%